PENINGKATAN EFISIENSI DAN PROTEKSI PENERAPAN TRANSAKSI PAYMENT GATEWAY BERBASIS QRIS PADA UMKM DI KOTA PANGKALPINANG - Fittriyyah, Fittriyyah; Julia, Julia; Vebstavili, Vebstavili (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
In this research, the aim is to find out whether there are transaction implementation and protection and efficiency constraints aimed at using QRIS-based Payment Gateway Technology among MSMEs in the city of Pangkalpinang and how to overcome these obstacles. This research uses qualitative research with a descriptive analysis approach. Data collection techniques use observation, interviews and documentation. Meanwhile, data analysis is carried out by data reduction, presentation and then drawing conclusions. To test the validity of the data using the triangulation method. The research results show that (1) The application of QRIS to MSMEs is generally in accordance with socialization about QRIS, but for everyday applications that occur among consumers, QRIS is still rarely implemented. (2) Obstacles that occur in implementing QRIS in MSMEs include signal or internet connection problems, as well as barcode errors that are not detected or not scanned on consumers' cellphones. (3) The impact of sales after using QRIS on MSMEs does not affect their sales turnover